Ethiopian Domestic Workers and Exploitative Labour in the Middle East: The role of social networks and gender in migration decisions - Moton, Lauren; Abeyta, Stephen; Dank, Meredith; Mulugeta, Tsigereda Tafesse (Anti-Trafficking Review, 2025)
Migrant domestic work in the Middle East is known for high rates of exploitative labour. Despite this fact, many women from Africa pursue this work as a gendered familial expectation or means of financial gain, among other motivations. In this article, we centralise how personal social networks—family, friends, peers, and communities—act as motivating factors for prospective migrant domestic workers in Ethiopia looking to travel for work in the Middle East. The analysis of 100 in-depth interviews with women migrant domestic workers seeking employment in the Middle East demonstrates that social networks and gender influence migration decisions in complicated, multifaceted, and sometimes contradictory ways. Social networks also play an important role in facilitating entry into domestic work for Ethiopian women and in seeking help when they experience exploitative conditions in the Middle East.